COP1 controls salt stress tolerance by modulating sucrose content. (31st December 2022) - Kim, Joo Yong; Lee, Seung Ju; Min, Wang Ki; Cha, Seoyeon; Song, Jong Tae; Seo, Hak Soo
ABSTRACT: The E3 ubiquitin ligase Constitutive Photomorphogenic 1 (COP1) plays evolutionarily conserved and divergent roles. In plants, COP1 regulates a large number of developmental processes including photomorphogenesis, seedling emergence, and gravitropism. Nevertheless, its function in abiotic stress tolerance remains largely unknown. Here, we demonstrate the role of COP1 in salt stress tolerance in Arabidopsis thaliana . In soil, cop1-4 and cop1-6 mutants were more tolerant to high salinity than wild-type (WT) plants during vegetative growth. However, in high salt-containing Murashige and Skoog (MS) medium, cop1-4 and cop1-6 seedlings exhibited significantly impaired growth compared with WT plants. Notably, cop1-4 and cop1-6 seedlings recovered their growth to the WT level upon exogenous sucrose treatment even under high salinity conditions. Compared with WT plants, the sucrose content of cop1-4 mutants was much higher at the vegetative growth stage but similar at the seedling stage. Upon exogenous sucrose supply, root elongation was significantly stimulated in cop1-4 seedlings but only slightly stimulated in WT plants. Thus, no significant difference was observed in root length between the two genotypes. Altogether, our data indicate that cop1 mutants are more tolerant to salt stress than WT plants, and the salt tolerance of cop1 mutants is correlated with their sucrose content.